2011
DOI: 10.5301/ijao.5000030
|View full text |Cite
|
Sign up to set email alerts
|

Toll-Like Receptors (TLRs) in Innate Immune Defense Against Staphylococcus Aureus

Abstract: Toll-like receptors (TLRs) are the most important class of innate pattern recognition receptors (PRRs) by which host immune and non-immune cells are able to recognize pathogen-associated molecular patterns (PAMPs). Most mammalian species have 10 to 15 types of TLRs. TLRs are believed to function as homo- or hetero-dimers. TLR2, which plays a crucial role in recognizing PAMPs from Staphylococcus aureus, forms heterodimers with TLR1 or TLR6 and each dimer has a different ligand specificity. Staphylococcal lipopr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(61 citation statements)
references
References 96 publications
1
55
0
5
Order By: Relevance
“…Several studies have suggested that bacterial Lpps are pathogen-associated molecular patterns (PAMPs) sensed by the mammalian host through Toll-like receptor 2 (TLR2) heterodimerized with TLR1 or TLR6 to induce innate immunity activation and to control adaptive immunity (9 -12). TLR2 plays a critical role in the host response to the Gram-positive bacteria Staphylococcus aureus (13) and Streptococcus agalactiae (14). Although TLR2 has been considered a receptor for various structurally unrelated PAMPs, recent studies have suggested that, via their lipid moiety, bacterial Lpps function as the major, if not the sole, ligand molecules responsible for TLR2 activation (15).…”
mentioning
confidence: 99%
“…Several studies have suggested that bacterial Lpps are pathogen-associated molecular patterns (PAMPs) sensed by the mammalian host through Toll-like receptor 2 (TLR2) heterodimerized with TLR1 or TLR6 to induce innate immunity activation and to control adaptive immunity (9 -12). TLR2 plays a critical role in the host response to the Gram-positive bacteria Staphylococcus aureus (13) and Streptococcus agalactiae (14). Although TLR2 has been considered a receptor for various structurally unrelated PAMPs, recent studies have suggested that, via their lipid moiety, bacterial Lpps function as the major, if not the sole, ligand molecules responsible for TLR2 activation (15).…”
mentioning
confidence: 99%
“…Toll-like receptors (TLRs) are the most important class of innate PRRs by which host immune and non-immune cells are able to recognize pathogen-associated molecular patterns (PAMPs) (Pietrocola et al 2011). TLR2 plays a crucial role in recognizing PAMPs from a lot of pathogens including S. aureus.…”
Section: Discussionmentioning
confidence: 99%
“…Lipopolysaccharides (LPS) of Gram-negative bacteria are recognized by TLR-4, which is essential in inducing the Gram-negative inflammatory response [12]. Several danger molecules have been identified in Gram-positive bacteria, including various lipoproteins and lipoteichoic acid (LTA), and some of these danger molecules are recognized by TLR-2 [13][14][15]. CD14 is a promiscuous co-receptor for a number of TLRs and facilitates the signalling of both TLR-4 and TLR-2 [11,15].…”
Section: Introductionmentioning
confidence: 99%